EFEKTIVITAS APLIKASI WATTPAD SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MINAT BACA - Sutarini Sutarini; Dara Fitrah Dwi (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This study specifically aims to describe the effectiveness of the Wattpad media in increasing reading interest in class XI students at SMK YPK Mabar Kec. Medan Deli. This research is a type of non-experimental quantitative research using the correlational method, namely research by assessing the relationship between two or more phenomena. The sample in this study was class XI SMK YPK Mabar as many as 20 students with simple random sampling technique. The instruments and techniques used to collect data in this study were non-test instruments consisting of questionnaires, interviews, observations, and documentation. Based on the results of the study, it is known that the overall score for the X variable (use of the Wattpad application) reaches 774 scores, while the Y variable (reading interest) reaches 869 scores. The correlation between the x variable and the y variable is 0.789 with a sufficient correlation interpretation because it is between 0.600 to 0.800. If rxy (calculated value) = 0.789 is significant by r table product moment with the number of N = 20 at a significant level of 5% = 0.444 and at a level of 1% = 0.561, it turns out that the value obtained through calculations is greater than rcount, namely 0.220 < 0.789 > 0.561. So it can be said that there is a significant relationship between the use of the Wattpad application on the reading interest of the YPK Mabar Vocational High School students.